PENGEMBANGAN E-MODUL BERBASIS PROBLEM BASED LEARNING PADA MATERI SISTEM PENCERNAAN MANUSIA UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF PESERTA DIDIK KELAS XI IPA SMA - Hafizah, Mutia; Sukmono, Tedjo; M.Haris Efendi Hsb (Universitas Islam Negeri Alauddin Makassar, 2023)
The purpose of this research is to develop learning media in the form of E-modules based on Problem Based Learning on human digestive system material to improve students' creative thinking skills which can be used in the learning process both online and offline. This development research uses the ADDIE development model which consists of Analysis, Design, Development, Implementation and Evaluation. Data collection was carried out using a questionnaire instrument and creative thinking pretest-posttest questions on 20 students at SMA Negeri 10 Sarolangun. The results of the expert validation show that the Problem Based Learning-based E-module that was developed is very feasible to use in the learning process at the trial stage. Teacher responses and student responses to the E-module being studied are very good to use. The test results show that the developed E-module is very good and feasible to use. Meanwhile, students' creative thinking skills have increased with the N-Gain value obtained which is in the category . This means that the E-module that is developed can effectively improve students' creative thinking skills. Further research is expected to be able to develop this Problem Based Learning-based E-module in other materials that are oriented towards creative thinking skills or other 21st century skills. Keywords: Development, E-module, Problem Based Learning, Creative thinking, Human Digestive System